Mapping District-Level Asbestos Exposure Risk in Java, Indonesia: Integrating Infrastructure, Demographics, and Seismic Vulnerability - Anna Suraya; Lelitasari; Uci Sulandari; Lulus Suci Hendrawati; Edwina Rudyarti; Yunita Sari Purba; Putri Winda Lestari; Defi Arjuni; Ida Ayu Pusfitasari; Diaz Rosita Dewi; Cantika Fariyah Rahmah; Nada Aqeel Faiz; et al. (International Journal of Environmental Research and Public Health, 2026)
(1) Background: Indonesia is one of the world’s largest consumers of asbestos, with widespread use of asbestos-cement roofing. Java Island, characterized by high population density and seismic vulnerability, presents a complex risk landscape for asbestos exposure. This study aimed to develop a district-level asbestos exposure risk map for Java by integrating asbestos roof prevalence, population density, and seismic hazard. (2) Methods: A descriptive, semi-quantitative approach was applied using secondary data from national statistics and geological hazard portals. Three variables—asbestos roof prevalence, population density, and seismic hazard—were categorized into five ordinal levels (very low to very high) and combined using GIS-based risk matrices to generate composite exposure risk maps. Sensitivity and statistical analyses were conducted to assess the robustness and internal consistency of the risk classification. (3) Results: Of 119 districts/municipalities, 43 (36%) were classified as very high risk and 45 (38%) as high risk under the primary GIS-based risk matrix classification. Major metropolitan corridors, including Greater Jakarta and Bandung, showed elevated risk where substantial asbestos use coincided with very high population density, whereas several southern and inland districts gained priority because of higher seismic hazard. Sensitivity analyses indicated that the classification was generally robust to moderate changes in weighting and threshold boundaries, although the predefined population density thresholds provided limited discrimination within Java. (4) Conclusions: Asbestos exposure risk in Java is both widespread and heterogeneous, shaped by the intersection of infrastructure, demographics, and seismic vulnerability. The map offers a practical tool for prioritizing asbestos control, public awareness campaigns, health surveillance, and disaster risk reduction measures in Indonesia.